2006
DOI: 10.1111/j.1460-9592.2005.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of ketorolac in neonates and infants after cardiac surgery

Abstract: Ketorolac was used safely in neonates and infants who have had cardiac surgery at our institution. Ketorolac was not associated with any adverse hematologic or renal effects. Prospective investigation is warranted to further assess the safety and effectiveness of ketorolac in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…A smaller, retrospective review of 10 infants younger than 6 months also demonstrated that ketorolac reduces the opioid requirement after abdominal surgery and can be administered safely to infants of 37 weeks CGA or greater [1]. The study of Papacci et al reviewed the use of ketorolac in a neonatal setting in 18 infants whose average CGA was 37 ± 4 weeks (range, 25-38 weeks) and found no significant changes in hematologic, renal, or hepatic parameters, and no resultant bleeding complications [7]. Although these conclusions appear promising for this very young age group, the numbers are quite small.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A smaller, retrospective review of 10 infants younger than 6 months also demonstrated that ketorolac reduces the opioid requirement after abdominal surgery and can be administered safely to infants of 37 weeks CGA or greater [1]. The study of Papacci et al reviewed the use of ketorolac in a neonatal setting in 18 infants whose average CGA was 37 ± 4 weeks (range, 25-38 weeks) and found no significant changes in hematologic, renal, or hepatic parameters, and no resultant bleeding complications [7]. Although these conclusions appear promising for this very young age group, the numbers are quite small.…”
Section: Discussionmentioning
confidence: 94%
“…The Food and Drug Administration has approved ketorolac for use in children older than 2 years, and data describing its safe use in infants older than 6 months have also been described [1,4,7]. Papacci et al [8] previously reported 18 neonates to whom ketorolac was administered in a postoperative or postprocedural setting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, there are a number of studies indicating that using ketorolac to manage postoperative pain in children after cardiac surgery does not increase the risk of postoperative bleeding (11,19,22,23). Similarly, in our patients no significant postoperative bleeding was noticed in the ketorolac in comparison to the paracetamol group.…”
mentioning
confidence: 44%
“…Aldrink JH et al (2011) state that neonates of less than 21 days may have increased risk for bleeding after intravenous ketorolac 25 . However many other studies demonstrated that intravenous ketorolac is safe to use in neonates in regard to bleeding manifestations [27][28] . The bleeding tendency may be transient due to temporary fall in platelet count in some patients 29 .…”
Section: Discussionmentioning
confidence: 99%